Using Participatory Workshops to Assess Alignment or Tension in the Community for Minimally Invasive Tissue Sampling Prior to Start of Child Mortality Surveillance: Lessons From 5 Sites Across the CHAMPS Network - Blevins, John (Clin Infect Dis, 2019)
The Child Health and Mortality Prevention Surveillance (CHAMPS) program is a 7-country network (as of December 2018) established by the Bill & Melinda Gates Foundation to identify the causes of death in children in communities with high rates of under-5 mortality. The program carries out both mortality and pregnancy surveillance, and mortality surveillance employs minimally invasive tissue sampling (MITS) to gather small samples of body fluids and tissue from the bodies of children who have died. While this method will lead to greater knowledge of the specific causes of childhood mortality, the procedure is in tension with cultural and religious norms in many of the countries where CHAMPS works—Bangladesh, Ethiopia, Kenya, Mali, Mozambique, Sierra Leone, and South Africa. Participatory Inquiry Into Community Knowledge of Child Health and Mortality Prevention (PICK-CHAMP) is a community entry activity designed to introduce CHAMPS to communities and gather initial perspectives on alignments and tensions between CHAMPS activities and community perceptions and priorities. Participants’ responses revealed medium levels of overall alignment in all sites (with the exception of South Africa, where alignment was high) and medium levels of tension (with the exception of Ethiopia, where tension was high). Alignment was high and tension was low for pregnancy surveillance across all sites, whereas Ethiopia reflected low alignment and high tension for MITS. Participants across all sites indicated that support for MITS was possible only if the procedure did not interfere with burial practices and rituals.